2016
DOI: 10.4103/0189-6725.182559
|View full text |Cite
|
Sign up to set email alerts
|

Our experience with pre-operative haemostatic assessment of paediatric patients undergoing adenotonsillectomy at Federal Medical Centre, Makurdi

Abstract: Background:In 2-4% of all patients requiring adenoidectomy, tonsillectomy or adenotonsillectomy, pre-operative screening tests for coagulation disorders are indicated to detect surgical bleeding complications. However, because of cost effect on the patients, the usefulness of these tests is being challenged. We therefore highlight our experience in paediatric patients undergoing adenoidectomy, tonsillectomy or both in our centre.Patients and Methods:This is a 3½-year analysis of the data of 165 paediatric pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…We found that the risk of bleeding is not higher in a patient with a positive coagulation test (some pathological values) or with a positive coagulation questionnaire. Many studies consider the coagulation questionnaire to be sufficient, effective, and more cost-effective than routinely performing laboratory coagulation tests [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the risk of bleeding is not higher in a patient with a positive coagulation test (some pathological values) or with a positive coagulation questionnaire. Many studies consider the coagulation questionnaire to be sufficient, effective, and more cost-effective than routinely performing laboratory coagulation tests [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative bleeding may uncover an undiagnosed bleeding disorder. Screening with general coagulation tests prior to the procedure have become common to assess bleeding risk in the perioperative period despite inconsistent data to support this practice 3–6 . ASH/ASPHO Choosing Wisely guidelines recommend against routine PT/PTT testing for otherwise healthy children without significant personal or family history of bleeding symptoms 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Screening with general coagulation tests prior to the procedure have become common to assess bleeding risk in the perioperative period despite inconsistent data to support this practice. [3][4][5][6] ASH/ASPHO Choosing Wisely guidelines recommend against routine PT/PTT testing for otherwise healthy children without significant personal or family history of bleeding symptoms. 7 PT and PTT are not sensitive tests for the diagnosis of the most common inherited bleeding disorders, including von Willebrand disease (VWD).…”
Section: Introductionmentioning
confidence: 99%